A study of the binding between radicicol and four proteins by means of spectroscopy and molecular docking. Issue 7 (July 2021) - Gan, Ya; Bai, Ning; Li, Xitong; Gao, Shuiting; Wang, Ruiyong
The interactions between radicicol and four proteins (catalase, trypsin, pepsin, and human serum protein) are investigated by spectroscopic techniques and molecular docking. A static quenching process is confirmed. The binding constant value between radicicol and human serum protein is the largest among the four proteins. Results reveal changes in the micro-environment of the protein by the addition of radicicol. It is found that radicicol shows an inhibitory effect on the activity of proteins (catalase, trypsin, and pepsin). Molecular docking results are consistent with the thermodynamic experimental results. This work provides clues to the elucidation of the mechanisms of the interactions between radicicol and proteins.